Implementasi Alat Sensor Pelampung Suar Berbasis Internet Of Things (Io T ) Pada Sarana Bantu Navigasi Pelayaran (SBNP) - Dwi Sasmita, Yanuar Rangga; Rakhman, Rizqi Aini; Yudianto, Prima Yudha; Nofandi, Faris (Innovative: Journal Of Social Science Research, 2025)
This study discusses the importance of Navigational Aids (SBNP) to ensure that vessels stay on a safe path when entering ports. A quantitative descriptive method with an Importance- Performance Analysis approach was used to measure the importance and performance of sensor tools based on ease, effectiveness, and credibility. The results show that the average importance value ranges from 4.0 to 5.0, while the performance value ranges from 3.3 to 4.7. Although the performance is quite good, several factors are still not optimal. The analysis shows that 6 out of 15 statements fall into the priority quadrant, indicating that some important factors meet user expectations, but improvements are needed in other areas. This study provides insights into the effectiveness and efficiency of SBNP in port navigation, with recommendations for performance improvements.